Development of efficient processes for multi-gram scale and divergent preparation of fluorous-Fmoc reagents. Issue 30 (29th July 2015) - Sugiyama, Yuya; Endo, Natsuki; Ishihara, Kazuki; Kobayashi, Yuki; Hamamoto, Hiromi; Shioiri, Takayuki; Matsugi, Masato
Abstract: An optimized, multi-gram scale synthesis of fluorous-Fmoc reagents is described. Fmoc reagents bearing C3 F7, C4 F9, and C6 F13 chains were prepared on multi-gram scale (ca. 1.0–7.0 g) in eight steps with overall yields of 73%, 60%, and 90%, respectively. The order of addition of the fluorous alkenes in a one-pot double tagging Heck reaction was also investigated in order to conduct an encoded mixture synthesis of f-Fmoc reagents. The target f-Fmoc reagents bearing C3 F7, C4 F9, and C6 F13 chains could be effectively separated based on the fluorine content of the molecules. Graphical abstract: